Improved Engagement Through Quizizz in Islamic Education at SMPIT Insan Kamil: Peningkatan Keterlibatan Melalui Kuis dalam Pendidikan Agama Islam di SMPIT Insan Kamil - Raditya Wisnu Pramudya; Nurul Latifatul Inayati (Academia Open, 2025)
General Background: The integration of digital technology in education has reshaped teaching methods, demanding adaptive and engaging strategies. Specific Background: In the field of Islamic Religious Education (PAI), conventional lecture-based methods often result in low student motivation and limited engagement. Knowledge Gap: Although gamification platforms like Quizizz have gained popularity, there is a lack of comprehensive studies on their effectiveness in integrated Islamic schools, particularly regarding not just motivation, but also participation and learning outcomes. Aims: This study aimed to evaluate the effectiveness of the Quizizz platform in enhancing motivation, participation, and academic performance in PAI classes at SMPIT Insan Kamil Karanganyar. Results: Findings reveal that systematic implementation of Quizizz significantly increased student motivation and learning outcomes, with an average post-test score improvement of 17 points. Novelty: Unlike prior studies focusing solely on motivation or primary school contexts, this research uniquely triangulates student, teacher, and document perspectives within an integrated Islamic school, offering a multidimensional analysis. Implications: While effective, Quizizz must be complemented with other pedagogical strategies to promote deeper conceptual understanding and intrinsic motivation. This study underscores the importance of blending digital innovation with reflective pedagogy in religious education.Highlight : Increased Motivation: 78% of students experienced an increase in learning motivation through Quizizz's points and leaderboard features. Improved Learning Outcomes: Students' average score increased from 62 to 79 after the use of Quizizz. Need for Combination of Methods: Quizizz is effective, but deep understanding still needs other approaches such as discussions or case studies. Keywords : Quizizz, Islamic Religious Education, Learning Motivation, Gamification, Learning Outcomes